Critical care management of hydrofluoric acid burns with a negative outcome. Issue 6 (23rd June 2021) - Prasad, Aalekh; Ibrahim, Heba; Mortimore, Katherine; Vandabona, Rohan
Abstract : Hydrofluoric acid is a highly corrosive acid widely used in various industries. When in contact with skin it causes local and systemic reactions due to the generation of fluoride ions. Severe burns are associated with high mortality rates, approaching 100%. We present a 21-year-old man with 15% full thickness burns, severe metabolic acidosis, hypoxia and electrolyte disturbances. The burns were treated with topical and subcutaneous injections of calcium gluconate, and the patient was given intravenous fluid, calcium chloride, magnesium and insulin-glucose infusions. Continuous renal replacement therapy was initiated due to the severity of the systemic toxicity. Extracorporeal membrane oxygenation was considered as it plays a vital role when conventional therapies fail. Our patient suffered multiple cardiac arrests and cardiopulmonary resuscitation was conducted several times but despite extensive efforts, he did not survive.